SOCIAL ACTORS IN AN INDONESIAN EFL CLASSROOM: A CRITICAL STUDY OF CLASSROOM INTERACTION - Nurul Hudadatun (TLEMC (Teaching and Learning English in Multicultural Contexts), 2020)
Wenden (2005) explained that representation social actor show how actor (people, or group) are represented in the discourse. In the previous studies there were several context about representation social actor, such as culture by lawless (2004) politic by Amer (2017), and lectures of people by Dashiti (2017). In this present study discussed about representation social actors in education context that focused on teachers as social actors by using content analysis as the design of the study and categorizations from van leuween (1996). Socio-semantic inventory also used to reveal the identities. Thus, the aim of this study is revealing the identities of two teacher during teaching English text in senior high school in Tasikmalaya. The finding showed that teacher identities that appear as in following: active teacher, powerful teacher, democratic teacher, facilitative teacher, and polite teacher. Thus, 5 identities found represented teacher identities in teaching English text in the classroom.